2022
DOI: 10.3390/microorganisms10112263
|View full text |Cite
|
Sign up to set email alerts
|

Roseburia intestinalis Modulates PYY Expression in a New a Multicellular Model including Enteroendocrine Cells

Abstract: The gut microbiota contributes to human health and disease; however, the mechanisms by which commensal bacteria interact with the host are still unclear. To date, a number of in vitro systems have been designed to investigate the host–microbe interactions. In most of the intestinal models, the enteroendocrine cells, considered as a potential link between gut bacteria and several human diseases, were missing. In the present study, we have generated a new model by adding enteroendocrine cells (ECC) of L-type (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…has increased with reports showing that the abundance of these bacteria is also reduced in individuals affected by inflammatory diseases and colorectal cancers. it was found that R. intestinalis supernatant induced a significant increase in peptide tyrosine tyrosine (PYY) and compared with B. fragilis, R. intestinalis produced more butyrate whereas B. fragilis secreted more propionate and acetate [75].…”
Section: Microorganisms In Large Intestinementioning
confidence: 99%
See 2 more Smart Citations

Digestibility of starch

Šárka,
Smrčková,
Sluková
2024
Preprint
“…has increased with reports showing that the abundance of these bacteria is also reduced in individuals affected by inflammatory diseases and colorectal cancers. it was found that R. intestinalis supernatant induced a significant increase in peptide tyrosine tyrosine (PYY) and compared with B. fragilis, R. intestinalis produced more butyrate whereas B. fragilis secreted more propionate and acetate [75].…”
Section: Microorganisms In Large Intestinementioning
confidence: 99%
“…resistant starch) and endogenous intestinal mucus supports the growth of specialist microbes that produce short chain fatty acids (SCFAs) and gases, causing the lowering of the pH and inhibiting pathogens [77]. Bacteroides spp., which constitute up to 30% of colonic microbiota, produce a variety of SCFAs [75]. SCFAs are vital metabolites primarily synthesized by anaerobic bacteria in the colon through the process of fermenting dietary fiber, and the type and concentration of SCFAs in the colon vary depending on the specific food consumed and the composition of the gut microbiome [1].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation

Digestibility of starch

Šárka,
Smrčková,
Sluková
2024
Preprint
“…Caco-2/HT29-MTX/NCI-H716/Raji-B: One quadricellular model representing the different cell types contributing to the protection of the intestinal barrier has been recently reported [ 158 ]. This model is complex since the addition of cells has to be performed in a certain order and at certain timepoints.…”
Section: Cellular Models Used To Test the Functionality Of The Intest...mentioning
confidence: 99%
“…The expression of MUC2, sucrase-isomaltase (SI), Matrix Metalloproteinase 15 (MMP15) and glucagon (GCG) can be assessed to confirm the presence and differentiation of the different cell types. However, little information was provided about this model for assessing its technical and functional relevance [ 158 ].…”
Section: Cellular Models Used To Test the Functionality Of The Intest...mentioning
confidence: 99%